Differentiation of physical and mechanical properties analysis of self made gypsum product with raw material from Tasikmalaya with standar ISO and factory made - AP, Wahyuning; Hasratiningsih, Zulia; Manurung, Rosida (Padjadjaran Journal of Dentistry, 2008)
In early research, gypsum’s product from Padalarang and Tasikmalaya had been compared and it is found that Tasikmalaya gypsum was better. In these research, it’s used gypsum product from Tasikmalaya with wet calcination method using autoclave. This research consisted of four samples divided into three control groups and one treatment group. Research’s sample consisted of 45 units and 15 units data from the last research. To compared physical and mechanical properties, every samples was tested in three treatments. Research results showed that the average setting time, setting expansion and compressive strength of wet calcination gypsum product are respectively 487.6 seconds, 0.492%, and 12.708 Mpa. The results were statistically analyzed with MANOVA and Tukey test. The analysis showed differences in physical and mechanical properties between self made gypsum product from Tasikmalaya with Padalarang’s and two marketed gypsum products. Setting time self made gypsum product meets the ISO for type III, while compressive strength and setting expansion were not. But gypsum’s production from Tasikmalaya done by wet calcinations had better physical and mechanical properties, so it can be used in dentistry.